The effects of customer and competitor orientations on performance in global markets: a contingency analysis - Zhou, Kevin Zheng; Brown, James R; Dev, Chekitan S; Agarwal, Sanjeev (Journal of International Business Studies, 2007)
Should companies adjust their orientations toward customers or toward competitors in global markets? To answer this question, we use contingency theory and examine how the effects of customer and competitor orientations on performance are moderated by different environmental conditions. Our results from the global hotel industry indicate that a customer orientation works better in economically developed markets, as well as in markets with good local business conditions, greater resource availability, and demanding customers. In contrast, a competitor orientation is more effective in markets that are economically developing, have poor local business conditions, and face resource scarcity.